2013
DOI: 10.1111/ctr.12248
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of arteriovenous fistula closure due to high‐output cardiac failure in kidney‐transplanted patients

Abstract: The necessity of shunt closure is not a rarity. Patients who underwent an AV fistula ligature had high access flows with about 2200 mL/min. As the symptoms of cardiac failure greatly improved after shunt closure, patients with high access flow may benefit from such an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…Echocardiographic data for our patients were also not available.The assessment of cardiac load was mostly clinical. This and our research shows that the need to close AVF in patients with kidney stones is not uncommon 59 30 . In our study of other reasons for the closure of AVF, except cardiac overload were aneurysmatic dilatation in 21% of them and hand oedema in 4% of patients, while in research conducted by Schier et al only two ligation were related to flow, but one was due to aesthetic reasons and the other due to infection 59 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Echocardiographic data for our patients were also not available.The assessment of cardiac load was mostly clinical. This and our research shows that the need to close AVF in patients with kidney stones is not uncommon 59 30 . In our study of other reasons for the closure of AVF, except cardiac overload were aneurysmatic dilatation in 21% of them and hand oedema in 4% of patients, while in research conducted by Schier et al only two ligation were related to flow, but one was due to aesthetic reasons and the other due to infection 59 .…”
Section: Discussionsupporting
confidence: 66%
“…Since the blood flow is faster through the AVF, which are on the upper arms but the forearms 60 , so is the "closure" of AVF in the research of Schier et al more often in those patients with AVFs on the upper arms.We do not have information on the exact localization of the AVF on hand for our patients and no data on the flow rate through the AVF. Vascular surgeons did not want to do the AVF ligation if there were no pathological findings in echocardiography in these patients, and the most common pathological findings on echocardiography were pulmonary hypertension and right ventricular dilatation 59 . Echocardiographic data for our patients were also not available.The assessment of cardiac load was mostly clinical.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important functions of hemodialysis is the removal of excess fluid from the body by means of ultrafiltration . In the current study, we found that body weight was significantly decreased at t − 30 than t + 30, which should be attributed to the removal of excess fluid by ultrafiltration.…”
Section: Discussionsupporting
confidence: 52%
“…15 Frequently, high-output failure can result from a known arteriovenous fistula used for hemodialysis in patients end-stage renaldisease. 16,17 A case of renal cell carcinoma causing systemic arteriovenous shunting and highoutput cardiac failure has also been described. 18 Signs and symptoms of renal arteriovenous fistulae include an abdominal bruit (100%), hypertension and cardiomegaly (50%), congestive heart failure (32%), and gross hematuria (21%).…”
Section: Discussionmentioning
confidence: 99%